Electromagnetic induction - Cohn, George I. (Electrical engineering (New York, N.Y.), 1949)
The flux linking law, ∊ = − dφ/dt, and the flux cutting law, ∊ = Bvl, often erroneously are considered as merely different ways of expressing the same phenomena. This article attempts to dispel the confusion surrounding the subject of electromagnetic induction.